2013
DOI: 10.1159/000343215
|View full text |Cite
|
Sign up to set email alerts
|

A Proposed Method to Comprehensively Define Outcomes in Acoustic Tumor Patients Undergoing CyberKnife Management

Abstract: Background: Vestibular assessment in patients with acoustic tumor (so-called vestibular schwannoma, VS) via ocular vestibular-evoked myogenic potential (oVEMP) and cervical VEMP (cVEMP) tests are not often discussed in the neurosurgical literature. Objectives: This study conducted physiological and morphological assessments for VS patients before and after CyberKnife radiosurgery. Methods: Twenty patients with unilateral VS underwent a battery of tests comprising facial nerve function test, audiometry, and cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…VEMPs were done systematically in patients suffering from vertigo or imbalance and an MRI centered on the IAC was requested in the case of isolated abnormal cervical or ocular VEMPs. Finally, cVEMPs and oVEMPs allow evaluation of the effects of treatment on VS patients who undergo stereotactic radiosurgery [21]. The role of the VEMPs in VS is not primarily in diagnosis, although some patients were detected this way.…”
Section: Discussionmentioning
confidence: 99%
“…VEMPs were done systematically in patients suffering from vertigo or imbalance and an MRI centered on the IAC was requested in the case of isolated abnormal cervical or ocular VEMPs. Finally, cVEMPs and oVEMPs allow evaluation of the effects of treatment on VS patients who undergo stereotactic radiosurgery [21]. The role of the VEMPs in VS is not primarily in diagnosis, although some patients were detected this way.…”
Section: Discussionmentioning
confidence: 99%
“…A recent investigation showed that the cVEMP test evaluates the ipsilateral sacculo-collic reflex, via the inferior vestibular nerve (IVN) to the motor neurons of the neck muscles. Both tests thus can be adopted in VS patients to assess the afflictions of SVN and IVN (Ushio et al 2009;Lin et al 2013b). Both tests thus can be adopted in VS patients to assess the afflictions of SVN and IVN (Ushio et al 2009;Lin et al 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…Although the condition of patients with multiple metastatic tumors may be timely controlled, oncolytic reaction and abnormal metabolism of bilirubin must be prevented during the early stages. Previous clinical trials reported that the hemogram was persistently normal during treatment with CyberKnife; however, the sudden decrease in granulocyte numbers after 2 weeks cannot be ignored, since it may lead to serious complications (7)(8). Thus, it is advocated to keep the patients who undergo CyberKnife therapy with more than two treatment plans hospitalized with symptomatic treatment for >2 weeks, until the hemogram returns to normal.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is a lack of theoretical basis and practical experience on deducing the additional dose and optimizing dosage. Due to its accuracy and flexibility, CyberKnife therapy may alleviate the pain symptoms, relieve the compression syndrome, improve the quality of life and increase the chances of overcoming advanced multiple tumors (2,7). In addition, CyberKnife exhibits significant radiosurgical value.…”
Section: Discussionmentioning
confidence: 99%